Childhood Determinants of Adult Psychiatric Disorder - Fryers, Tom (Bentham Open, 2013)
The aim of this project was to assess the current evidence from longitudinal studies for childhood determinants of adult mental illness. Because of the variable and often prolonged period between factors in childhood and the identification of mental illness in adults, prospective studies, particularly birth cohorts, offer the best chance of demonstrating associations in individuals. A review was undertaken in 2006 of the published literature from longitudinal studies, together with some large-scale retrospective studies and relevant reviews which provided supplementary evidence. The main focus was upon potentially ameliorable characteristics, experiences or situations of childhood; however, other factors, not determinants but pre-cursors, associated with later mental illness could not be left out. Seven major electronic data-bases of published research were interrogated with a range of key-words and the results supplemented from personal searches, enquiries and reference trails. In excess of 1,500 abstracts were read to select 250 papers for full review. The material was assessed in relation to ten factors: Psychological disturbance; Genetic Influences; Neurological Deviance; Neuroticism; Behaviour; School Performance; Adversity; Child Abuse or Neglect; Parenting and parent-child relationships; Disrupted and Disfunctional Families. In 2011 the search was repeated for the period 2006 to mid-2011, using the same search terms and supplemented in the same manner. Over 1,800 abstracts emerged and almost 200 papers selected for more detailed review. These were then integrated into the original text with modifications where necessary. The whole text was then revised and edited in January / February 2012. There is continuing evidence for the association with later mental ill-health for each of these ten factors, but with different degrees of conviction. The evidence for each is discussed in detail and weighed both separately and in relation to others. These are then summarised, and the research implications are considered. Finally, the implications for prevention are discussed together with the practical potential for preventive and health-promoting programmes.